2014
DOI: 10.1002/mc.22254
|View full text |Cite
|
Sign up to set email alerts
|

The proto‐oncogene PBF binds p53 and is associated with prognostic features in colorectal cancer

Abstract: The PTTG1-binding factor (PBF) is a transforming gene capable of eliciting tumor formation in xenograft models. However, the precise role of PBF in tumorigenesis and its prognostic value as a cancer biomarker remain largely uncharacterised, particularly in malignancies outside the thyroid. Here, we provide the first evidence that PBF represents a promising prognostic marker in colorectal cancer. Examination of a total of 39 patients demonstrated higher PBF expression at both the mRNA (P ¼ 0.009) and protein (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 56 publications
1
36
1
Order By: Relevance
“…The precise role of PBF in tumor cell invasion remains poorly understood in breast, thyroid, and colorectal cancer cells (1518). We therefore sought to investigate the ability of PBF to induce invasion across a panel of cancer cells (Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise role of PBF in tumor cell invasion remains poorly understood in breast, thyroid, and colorectal cancer cells (1518). We therefore sought to investigate the ability of PBF to induce invasion across a panel of cancer cells (Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, high PBF promoter activity was associated with poorer clinical outcome and increased metastatic risk in breast cancer (17). Thirdly, colorectal tumors with higher PBF protein expression demonstrated greater vascular invasion (18). Thus, it is possible that PBF is integral to tumor cell invasion in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…colorectal (McCabe et al 2003, Stratford et al 2005, Watkins et al 2010, Read et al 2014. PBF has been reported to repress radioiodide uptake in thyroid cancer cells by binding to NIS, which leads to NIS internalisation and inhibition of function (Smith et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It soon became apparent that PTTG and PBF are involved in other endocrine tumours, and I identified that overexpression of PTTG and PBF are markers of prognosis in thyroid cancer, independent of patients' age and gender and of tumour type and size (Boelaert et al 2003a, Stratford et al 2005. Subsequent studies in our group have confirmed overexpression in other endocrine-related neoplasia including colon (Read et al 2016) and breast cancers (Boelaert & Franklyn 2003, Watkins et al 2010. Further functional investigations have unravelled some of the mechanisms through which these genes signal indicating roles in the initiation (Kim et al 2005) as well as the promotion of tumourigenesis through the upregulation of pro-mitogenic and pro-angiogenic growth factors (Kim et al 2006a,b).…”
mentioning
confidence: 86%